Methanobactins: Maintaining copper homeostasis in methanotrophs and beyond - Kenney, Grace E. (J Biol Chem, 2018)
Methanobactins (Mbns) are ribosomally produced, post-translationally modified natural products that bind copper with high affinity and specificity. Originally identified in methanotrophic bacteria, which have a high need for copper, operons encoding these compounds have also been found in many non-methanotrophic bacteria. The proteins responsible for Mbn biosynthesis include several novel enzymes. Mbn transport involves export through a multidrug efflux pump and re-internalization via a TonB-dependent transporter. Release of copper from Mbn and the molecular basis for copper regulation of Mbn production remain to be elucidated. Future work is likely to result in the identification of new enzymatic chemistry, opportunities for bioengineering and drug targeting of copper metabolism, and an expanded understanding of microbial metal homeostasis.